Religion in the public sphere: Canadian case studies - Lefebvre, Solange; Beaman, Lori G. (University of Toronto Press, 2014)
"The place of religion in the public realm is the subject of frequent and lively debate in the media, among academics and policymakers, and within communities. With this edited collection, Solange Lefebvre and Lori G. Beaman bring together a series of case studies of religious groups and practices from all across Canada that re-examine and question the classic distinction between the public and private spheres